Therapeutic Lifestyle Strategies Taught in U.S. Pharmacy Schools - Thomas L. Lenz, PharmD, MA; Michael S. Monaghan, PharmD; Elizabeth A. Hetterman (Centers for Disease Control and Prevention, 2007)
IntroductionSeveral organizations representing pharmacy and other health professions stress the importance of teaching public health topics as part of training future practitioners. The objective of our study was to assess the number of U.S. pharmacy schools that incorporate lifestyle modification topics into their curricula.MethodsWe developed an electronic survey on lifestyle modification topics and sent it to each of the 89 pharmacy schools in the United States. The survey defined lifestyle modification topics as topics that address nutrition, exercise, weight loss, smoking cessation, and alcohol use.ResultsOf 89 pharmacy schools contacted, 50 (56%) responded to the survey. Of the 50, four offer at least one required course in a lifestyle modification topic, seven offer at least one elective course, and one offers a required course that incorporates more than one lifestyle modification topic. Five required and nine elective courses were identified from the responses. Nutrition was the most commonly offered required course topic, followed by smoking cessation, exercise, weight loss, and alcohol use.ConclusionFew pharmacy schools are addressing recommendations to promote public health education through formalized didactic courses. More courses on lifestyle modification topics should be offered to pharmacy students, who will be highly accessible to the public as pharmacists and will be able to offer education to enhance public health focused on the prevention of chronic diseases.